Integrative transport policy - theory and practice - Anna Mężyk (Przegląd Komunikacyjny)
The availability of transport services is one of the basic conditions for meeting the living needs and socio-economic activity of the population. The lack of access to such services is called a communication exclusion. Analyzes indicate that in Poland, both the number and the length of bus lines, mainly regional bus lines, are systematically decreasing. There is also little interest of local government units in building a common public transport offer. At the same time, the automotive index is rising. An important condition for shaping an integrated public transport network is cooperation: cooperation of various authorities at different levels, cooperation of authorities with carriers, cooperation with residents, enabling them to obtain their opinions. An important role can and should be played by non- governmental organizations that exist and operate in many places in Poland, pointing to the desired and expected solutions in the area of transport, e.g. the course of bicycle routes or the location of transfer points, or pointing to shortcomings and deficiencies in infrastructure. Keywords: Transport policy; Availability of transport services